2018
DOI: 10.32474/madohc.2018.02.000127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Amoxicillin with Clavulanic Acid Antibiotic Premedication on Pre-Treatment and Post-Endodontic Pain in Teeth with Irreversible Pulpitis: A Randomized. Controlled Trial

Abstract: The purpose of this randomized, double-blind, controlled study was to assess the effect of antibiotic premedication on pre treatment and post opertive pain after endodontic treatment. Forty two patients with symptomatic irreversible pulpitis were randomized and allocated to experimental and placebo groups where the experimental group received the antibiotic premedication. Degree of pain was measured by the number of analgesics needed in addition to a four step pain scale before initiation of endodontic treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Abielhassan et al (9) established that amoxicillin with clavulanic acid pre-medication could be prescribed to lessen the degree of post-operative pain after endodontic treatment. Ramazani et al (25) assessed post-operative pain after endodontic treatment of molar teeth with irreversible pulpitis and noticed that pre-medication with ibuprofen caused significantly greater pain reduction compared to zintoma and placebo at point of time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Abielhassan et al (9) established that amoxicillin with clavulanic acid pre-medication could be prescribed to lessen the degree of post-operative pain after endodontic treatment. Ramazani et al (25) assessed post-operative pain after endodontic treatment of molar teeth with irreversible pulpitis and noticed that pre-medication with ibuprofen caused significantly greater pain reduction compared to zintoma and placebo at point of time.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, individual use of antibiotic as a pre-medication has less effect on post-obturation pain. Abielhassan et al (9) concluded that amoxicillin with clavulanic acid antibiotic pre-medication could be prescribed to lessen the degree of post-operative pain after endodontic treatment. On the contrary, Pickenopaugh et al (14) determined the effect of amoxicillin on endodontic flare-up in asymptomatic necrotic teeth and concluded that prophylactic amoxicillin had no effect on the occurrence of flare-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation